2018
DOI: 10.3233/adr-170051
|View full text |Cite
|
Sign up to set email alerts
|

The Bri2 and Bri3 BRICHOS Domains Interact Differently with Aβ42 and Alzheimer Amyloid Plaques

Abstract: Alzheimer’s disease (AD) is the most common form of dementia and there is no successful treatment available. Evidence suggests that fibril formation of the amyloid β-peptide (Aβ) is a major underlying cause of AD, and treatment strategies that reduce the toxic effects of Aβ amyloid are sought for. The BRICHOS domain is found in several proteins, including Bri2 (also called integral membrane protein 2B (ITM2B)), mutants of which are associated with amyloid and neurodegeneration, and Bri3 (ITM2C). We have used m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 47 publications
0
32
0
Order By: Relevance
“…BRICHOS is a recently established molecular chaperone domain, which efficiently prevents fibrillar amyloid aggregation as well as its associated toxicity, as shown in vitro, in mouse hippocampal slice preparations, and in Drosophila models 19,23,26,27,32,34,35 . The dementia relevant Bri2 and its BBB permeable BRICHOS domain are associated with AD: Bri2 is produced in the CNS in the same cells as the Aβ precursor protein AβPP, colocalizes with senile plaques, interacts with Aβ in neurons, and increased amounts of different Bri2 forms have been found in human AD brains 38,39,48 . Further preclinical work that focus on the potential usefulness of Bri2 BRICHOS delivery and/or activation for prevention and treatment of AD should be pursued in relevant animal models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BRICHOS is a recently established molecular chaperone domain, which efficiently prevents fibrillar amyloid aggregation as well as its associated toxicity, as shown in vitro, in mouse hippocampal slice preparations, and in Drosophila models 19,23,26,27,32,34,35 . The dementia relevant Bri2 and its BBB permeable BRICHOS domain are associated with AD: Bri2 is produced in the CNS in the same cells as the Aβ precursor protein AβPP, colocalizes with senile plaques, interacts with Aβ in neurons, and increased amounts of different Bri2 forms have been found in human AD brains 38,39,48 . Further preclinical work that focus on the potential usefulness of Bri2 BRICHOS delivery and/or activation for prevention and treatment of AD should be pursued in relevant animal models.…”
Section: Discussionmentioning
confidence: 99%
“…Recombinant human (rh) BRICHOS domains from proSP-C and Bri2 are efficient inhibitors also of amyloid formation of non-client proteins, such as medin, islet amyloid polypeptide (IAPP), Aβ40, and Aβ42 [33][34][35] . Bri2, mutations of which give rise to amyloid formation and familial British and Danish dementias, is produced in the central nervous system (CNS), with expression in neurons of the hippocampus and cortex in humans 36,37 , and colocalizes with senile plaques in AD patients 38,39 . Under physiological conditions, the BRICHOS domain is released by proteolysis from the Bri2 precursor protein 33,38,40 .…”
mentioning
confidence: 99%
“…Using these kinetic analyses, Cohen and colleagues have shown that a molecular chaperone, a human BRICHOS domain, delayed toxicity in brain mouse tissue [80]. The Bri2 protein is produced in the central nervous system, in the same cells as the Aβ precursor protein, APP, and colocalizes with senile plaques, interacts with Aβ in neurons, and increased amounts of different Bri2 forms have been found in human AD brains [81,82]. Interestingly, other researchers have found that the BRICHOS domain from the Bri2 chaperone is BBB permeable, reaching the brain parenchyma after peripheral administration [83].…”
Section: Mechanisms Involved In Transthyretin Neuroprotection In Alzhmentioning
confidence: 99%
“…Although proSP-C is exclusively expressed in the alveolar epithelium (21,22), Bri2 is ubiquitously expressed, and in the brain it is particularly abundant in CA1 pyramidal neurons (23,24). Altered levels of Bri2 together with its processing enzymes and the homologue Bri3 (also called ITM2C) have been detected in the hippocampus of post-mortem AD cases (25,26). Furthermore, the secreted Bri2 BRICHOS domain has been found to be associated with amyloid plaques (25).…”
mentioning
confidence: 99%